1971
DOI: 10.1021/jo00822a002
|View full text |Cite
|
Sign up to set email alerts
|

Carboxysilanes and -germanes. III. Ionization constants of triorganosilane- and triorganogermanecarboxylic acids in ethanol-water and dimethyl sulfoxide media

Abstract: Ionization constants of the following carboxylic acids have been determined by a spectrophotometric method: MenPh3 -"MC02H, where M = C, Si and Ge, = 0-3, in ethanol-water media and where M = C and Ge, in dimethyl sulfoxide; (XCeH4)3GeC02H, where X = H, p-Me, m-Me, p-OMe, m-OMe, p-F, m-F, and p-CFs, in ethanol-water media and X = H, p-Me, m-Me, p-OMe, in dimethyl sulfoxide. The relative order of acidity, R3Si-C02H » RsGeCOaH > R3CC02H, is explained in terms of ( -d) bonding between the orbitals of the C02_ gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The 5- exo cyclization rate constants of the aromatic acylgermanes correlate roughly linearly with the p K a value of the acids (XC 6 H 4 ) 3 GeCOOH as well as with the Hammett constant σ para . Plots of the cyclization rate constants against the 13 C NMR chemical shifts of the respective carbonyl carbon are also nearly linear (graphs shown in the Supporting Information).…”
Section: Resultsmentioning
confidence: 81%
“…The 5- exo cyclization rate constants of the aromatic acylgermanes correlate roughly linearly with the p K a value of the acids (XC 6 H 4 ) 3 GeCOOH as well as with the Hammett constant σ para . Plots of the cyclization rate constants against the 13 C NMR chemical shifts of the respective carbonyl carbon are also nearly linear (graphs shown in the Supporting Information).…”
Section: Resultsmentioning
confidence: 81%
“…The driving force for the TBP deformation of the copper(II) triphenylacetate dimer may be the intermolecular nonbonded repulsions of the bulky triphenylmethyl groups. The cage structure of this complex is expected to be more flexible than that of the acetates, because of the greater acidity of Ph3CCOOH compared with CH3COOH (pKa values of Ph3CCOOH and CH3COOH in dimethyl sulfoxide solutions are 9.29 and 11.41, respectively; Steward, Dziedzic, Johnson & Frohliger, 1971). Thus, the bulkiness of the substituent groups on the bridges and the weak- only structural data with R values less than 0.06 are presented.…”
Section: Molecular Structurementioning
confidence: 99%
“…Silacarboxylic acids have been experimentally found to be efficient carbon monoxide-releasing molecules and used, for instance, in the synthesis of bioactive molecules . In this regard, silacarboxylic and germacarboxylic acids have been previously reported. , It has also been indicated that silacarboxylic acids are demonstrated to be easy to handle, air-stable, and efficient carbon monoxide precursors . This has been demonstrated in the synthesis of important bioactive compounds such as HIV-1 inhibitor .…”
Section: Resultsmentioning
confidence: 98%